PENGARUH TAYANGAN IKLAN TELEVISI L-MEN VERSI THE SHOOT, TERHADAP BRAND IMAGE DIKALANGAN ANGGOTA FITNES DIAMOND TANGERANG - Tony, Tony (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2014)
Gym is one of the sports that require a fee . Not only for health and body fitness course , fitness is also a major goal for most people in shaping the muscles of the body in order to appear ideal even slimming. From the start of a long time of exercise , eating rules , types of supplements that must have been consumed in the set by an instructor or coach . it is necessary for dietary supplements as supporters . L -Men is one type of milk beverage supplements for those who exercise . L -Men are not the only dairy brand supplements on the market . Realizing various brands of products and competition in the market , then the company will not cease promotion to establish communication with the consumer . Promotion in the L -Men do one through the electronic media , namely television . The purpose of this study was : ( 1 ) To determine ad impressions L -Men in the television version of The Shoot and brand image of L -Men . ( 2 ) Determine the effect of L -Men commercials on television to brand image among members of Fitness Diamond Tangerang . With explanative method with a quantitative approach . The results of this study to determine the benefits for the development of communication , especially in the field of advertising that is based on ethics , manners and manner of advertising in Indonesia.